Economic Geographical Aspects of Agriculture, Forestry and Fishing Development of Andizhan Region - M. Mamajonov; B. B. Dehqonov (International Journal on Integrated Education, 2022)
the article provides information on the development and systematic implementation of the agricultural sector in the Andijan region, issues of cultivation, increasing the efficiency of agricultural production, the importance of grown products in meeting the needs of the population, as well as in saturating domestic and foreign markets. The article expresses the opinion about four agrochemical zoning of the territory of the region for the proper effective development of agriculture in the region, which is one of the most important factors in the development of the industry.